Pengaruh IAA dan Urutan Daun Terhadap Pertumbuhan Tunas Tanaman Anggrek Cattleya sp. - Lubis, Anita Agustina; Harahap, Fauziyah (Bioscientist : Jurnal Ilmiah Biologi, 2024)
Orchids are ornamental plants that have high aesthetic value and beauty. Many human activities use this plant, including weddings, Christmas, New Year and birthdays. Orchid propagation can be done conventionally, but it requires a large area of land and takes a long time to grow. However, it can also be multiplied using tissue culture. Plant tissue culture techniques have better prospects than conventional propagation because tissue culture can produce large numbers of new plants without being influenced by time or season. This research aims to determine the effect of IAA and leaf order on shoot growth of Cattleya sp orchid plants. This type of research is experimental research with a Factorial Completely Randomized Design (CRD) with 12 treatments and 3 replications. There are 2 factors in this study, namely factor I PGR IAA (0, 0.5 mg/l, 1 mg/l, and 1.5 mg/l) and factor II Leaf order (1st leaf, 2nd leaf, and 3rd leaf). This research is a quantitative descriptive study with the parameters of the time of shoot emergence and using 2-way Statistics with Analysis of Variance (ANOVA) with the parameters of number of shoots, number of leaves (strands), and plantlet height. From the research results, it was found that the administration of IAA (Indole Acetic Acid) and the order of the leaves did not have a real effect on the number of shoots, number of leaves (strands) and plantlet height. However, the best treatment is the I0.5D2 treatment (IAA 0.5 mg/l and 2nd leaf).